Long-range charge order on the Fe3O4(001) surface - SHVETS, IGOR; MARIOTTO, GUIDO; MURPHY, SHANE; KANTOR, ROMAN (American Physical Society, 2004)
The Verwey transition in magnetite is of fundamental importance for the understanding of metal-insulator transitions but, in spite of being the subject of many studies over the last century, its nature is not fully understood. This is even more true in the case of the magnetite surface, where the low dimensionality plays an additional role in the determination of the Verwey transition temperature. We have atomically resolved the (?2??2)R45? reconstructed surface by scanning tunneling microscopy and we have modeled our experimental results by density functional theory calculations. We attribute the observed pattern to the charge ordering of Fe2+-Fe2+ and Fe3+-Fe3+ dimers. We propose a mechanism for the formation of this charge ordered surface and provide an explanation for the increase of the Verwey transition temperature at the (001) surface of magnetite.
PUBLISHED
Keywords: Surface Physics; Verwey transition